Proceedings of the second international congress on Islamic civilisation in Southern Africa, March 2016, Durban (İstanbul)
223 sayfa
Keywords: “The international congress on “Islamic Civilisation in Southern Africa” was organized by IRCICA, the Awqaf South Africa (Awqaf SA), the University of Kwazulu-Natal (UKZN ) and the International Peace College South Africa (IPSA), in Durban, South Africa, on 4-6 March 2016. Media institutions from South Africa contributed to the organization of the congress namely ITV, Radio Al Ansaar and Minara Chamber of Commerce. Within the framework of IRCICA’s activities, this was the second congress on this theme after the symposium which was held in 2006 in Johannesburg (organized by IRCICA, Awqaf SA and the University of Johannesburg). The Durban congress received contributions of studies from academics, media specialists and editors, representatives of community establishments. The participants came from Botswana, Uganda, usa, South Africa and Zimbabwe. The subjects of history and culture touched upon in the congress encompassed the whole Southern Africa region“ --